Dynamics and stability results of fractional pantograph equations with complex order - Vivek, D.; Kanagarajan, K.; Harikrishnan, S. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we study the existence, uniqueness and stability of solutions for fractional pantograph equations with complex order. The Krasnoselkii’s fixed point theorem and Banach contraction principle are used to obtain the desired results.